(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Women entrepreneurship plays a significant role in the economic development of a region. This study aims to analyse the challenges faced by women entrepreneurs and explore the prospects for their growth and success. The research methodology involves a combination of quantitative and qualitative approaches, including surveys, interviews, and case studies. The study identifies various problems faced by women entrepreneurs, such as limited access to finance, lack of family support, societal stereotypes, and difficulties in balancing work and family responsibilities. Despite these challenges, the study also highlights several prospects for women entrepreneurs, including government support programs, access to new markets through digital platforms, and changing societal attitudes towards women in business. The findings of this study have important implications for policymakers, business support organizations, and women entrepreneurs themselves. By addressing the challenges identified and capitalizing on the prospects available, women entrepreneurs in can overcome barriers to their success and contribute significantly to the local economy.